Electrochemical deposition of cadmium telluride films - Klochko, N.P.; Volkova, N.D.; Dobrotvorskaya, M.V.; Kopach, V.R.; T.A. Li (Functional Materials, 2008)
The mechanisms of electrochemical processes in the electrolyte for cadmium telluride semi-conducting film deposition and in corresponding partial solutions containing cadmium and tellurium ions have been studied by voltammetry with linear potential scanning and by cyclic voltammetry. The differences between cathodic processes on chemically inert titanium nitride substrates and catalytically active molybdenum surface have been revealed. Basing on these studies, the nature of impurities discovered in this work by X-ray photoelectron spectroscopy at the surface and inside the cadmium telluride films deposited on molybdenum and titanium nitride surfaces has been explained. The latter made it possible to select the electrodeposition parameters and the substrate material which provide the stoichiometric film composition.